PHASE TRANSFORMATION IN WEAR-RESISTANT MICROALLOYED CHROME-MANGANESE ALLOYS OF TRANSIENT CLASS AND THEIR MECHANISMS - G. V. Levchenko; V. L. Pljuta; A. M. Nesterenko; A. B. Sychkov (Литьë и металлургия, 2011)
The comparative analysis of regularities of phasestructural transformations at high-temperature thermal processing in complex doped alloy of a transitive class of system Fe-Mn-Cr-Ti-V-C is given.